Exploring 2016–2017 surface ozone pollution over China: source contributions and meteorological influences - Lu, Xiao; Zhang, Lin; Chen, Youfan; Zhou, Mi; Zheng, Bo; Li, Ke; Liu, Yiming; Lin, Jintai; Fu, Tzung-May; Zhang, Qiang (Atmospheric chemistry and physics, 2019)
Severe surface ozone pollution over major Chinese cities has become an emerging air quality concern, raising a new challenge for emission control measures in China. In this study, we explore the source contributions to surface daily maximum 8 h average (MDA8) ozone over China in 2016 and 2017, the 2 years with the highest surface ozone averaged over Chinese cities in record. We estimate the contributions of anthropogenic, background, and individual natural sources to surface ozone over China using the GEOS-Chem chemical transport model at 0.25∘×0.3125∘ horizontal resolution with the most up-to-date Chinese anthropogenic emission inventory. Model results are evaluated with concurrent surface ozone measurements at 169 cities over China and show generally good agreement. We find that background ozone (defined as ozone that would be present in the absence of all Chinese anthropogenic emissions) accounts for 90 % (49.4 ppbv) of the national March–April mean surface MDA8 ozone over China and 80 % (44.5 ppbv) for May–August. It includes large contributions from natural sources (80 % in March–April and 72 % in May–August). Among them, biogenic volatile organic compound (BVOC) emissions enhance MDA8 ozone by more than 15 ppbv in eastern China during July–August, while lightning NOx emissions and ozone transport from the stratosphere both lead to ozone enhancements of over 20 ppbv in western China during March–April. Over major Chinese city clusters, domestic anthropogenic sources account for about 30 % of the May–August mean surface MDA8 ozone and reach 39–73 ppbv (38 %–69 %) for days with simulated MDA8 ozone > 100 ppbv in the North China Plain, Fenwei Plain, Yangtze River Delta, and Pearl River Delta city clusters. These high ozone episodes are usually associated with high temperatures, which induce large BVOC emissions and enhance ozone chemical production. Our results indicate that there would be no days with MDA8 ozone > 80 ppbv in these major Chinese cities in the absence of domestic anthropogenic emissions. We find that the 2017 ozone increases relative to 2016 are largely due to higher background ozone driven by hotter and drier weather conditions, while changes in domestic anthropogenic emissions alone would have led to ozone decreases in 2017. Meteorological conditions in 2017 favor natural source contributions (particularly soil NOx and BVOC ozone enhancements) and ozone chemical production, increase the thermal decomposition of peroxyacetyl nitrate (PAN), and further decrease ozone dry deposition velocity. More stringent emission control measures are thus required to offset the adverse effects of unfavorable meteorology, such as high temperature, on surface ozone air quality.